Energy-based break-even transportation distance of biomass feedstocks - Tumuluru, J. S.; Igathinathane, C.; Archer, D.; McCulloch, R. (Frontiers in Energy Research, 2024)
It is critical to evaluate the distance, a solid biomass feedstock when used as biobased fuel can drive the transport from its energy content, for transportation analysis, and this information is not available. The breakeven distance (BED) of various fuels from biomass feedstocks and fossil sources was analyzed for truck, rail, and ship transportation modes based on bulk density, moisture content, and specific energy. Fourteen different biomass feedstocks, such as crop residues (e.g., corn stover), woody biomass (e.g., wood chips), thermally pretreated (torrefied), densified forms (pellets), and cattle feedlot compost; as well as standard fossil fuels (3), such as coal, lignite, and diesel were considered for BED analysis and comparison. The BED values were derived by comparing the energy content of biomass feedstocks with the energy expended on transporting the fuels through selected transportation modes. For ready reference, an alternative derivation of BED equations and example calculations are also presented. Among the biomass feedstocks, torrefied pellets had the highest BED (4.16×10^4, 12.47×10^4, and 54.14×10^4 km) and cattle feedlot compost had the lowest BED (1.29×10^4, 3.88×10^4, and 9.23×10^4 km) respectively for truck, rail, and ship. Higher bulk density and higher specific energy of the biomass feedstocks increased the BED for all modes of transport. Bulk density limits of biomass feedstocks after which the transports become the efficient mass-limited transportation are 223, 1480, and 656 kg/m^3 for truck, rail, and ship, respectively. Truck transport is typically mass-limited (payload limit restriction; increased BED), whereas rail transport is entirely volume-limited (cargo space restriction; decreased BED), and ship transport is mostly volume-limited for biomass feedstocks and mass-limited for densified biomass feedstocks. Ship transport is the most efficient, followed by rail and truck; and on average for the materials (17) studied, rail is 3.1 times and ship is 9.2 times the truck's BED. Based on the bulk density and higher specific energy of the biomass feedstocks, regardless of the refinery location, interstate truck transportation of these feedstocks was not a limiting factor in the bio-refining process, with the studied biomass feedstocks BED per truckload represent between 0.89 and 2.88 times the US perimeter.